JARINGAN USAHA PERAJIN KERAMIK ( Studi Kasus di Desa Klampok, Kecamatan Purworejo Klampok, Kabupaten Banjarnegara, Jawa Tengah) - , ERISA HANA DITA SUGIANTO; , Dr. Suharko, S.Sos. M.si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The developing countries, such as Indonesia, still relies heavily on the agricultural sectors and the small business sectors. Therefore, in economic activity, the survival and the growth of small businesses is interesting to be studied. The number of domestic industries in Indonesia makes these entrepreneurs should be able to keep abreast of the times which happen. However from many crafts, there is handicraft whose existence is only one in the area, one of which is ceramic craft in Klampok Banjarnegara. With the problem formulation \"how to network of crafters in ceramic crafts and development of business in ceramic crafts until nowâ, researcher is trying to find a link between the social networks formed by the development of business by ceramic crafters in Klampok village. This research also aims to look at the entrepreneurs, entrepreneur-crafters and crafters, so it can grow today and to know a social network which they form with regard to the development of their business. The method of this research used is included in the category of qualitative research with case study method. Type of case study used in this research is a intrinsic case study, this research are to doing with special caracteristic of case study and unique case study which are formed between the ceramic crafters in Klampok and the development of business. A intrisic case study itself is chosen because the researcher can understand better and it can describe the problems which become the object of its research. From this research, it is obtained two data, namely the primary data based on interviews with employers, entrepreneurscrafters and ceramic crafters and observations conducted in the center of ceramic crafts in Klampok village. Whereas, secondary data is obtained from the documentation of printing and electronic media. By using the theory of Social Network and the Embeddedness Concept can be concluded about the connection of social network with the progress of the business formed between entrepreneurs, entrepreneur-crafters and crafters in Klampok village. This social network is initially formed from the establishment of Meandallaei ceramic which later inspires the establishment of Mustika ceramic and Usaha Karya. From here, the social network among entrepreneurs of the ceramic pottery in Klampok is formed. Then it starts becoming an attraction for other rural communities in Klampok for founding business and it is established the wider network among entrepreneurs of ceramic crafts. From the formation of social networks among the entrepreneurs of ceramic crafts, it makes their businesses can grow until now because they are attached in the social network. The more extensiive social network which is formed, so the more progress business they endure. The more limited social network which is formed, so peopleâs attempt is more difficult to make the progress